How can service quality, patient value, and patient satisfaction increase hospital patient loyalty? - Guspianto Guspianto; Muthia Mutmainnah; Wahyu Indah Dewi Aurora (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Patient loyalty will be created if the hospital is able to provide quality services that create the best values for patients thereby increasing patient satisfaction.Failure to understand quality of service, patient value, and patient satisfaction will risk losing patient loyalty to hospital services. This study aims to analyze the model of hospital patient loyalty as the effect of service quality, patient value and patient satisfaction. A cross sectional study was conducted through a survey among inpatients at eight hospitals in Jambi Province-Indonesia. A four-point likert scale was used to measure construct variables and analyzed using Partial Least Squares-Structural Equation Model. The results showed that the influence between factors in the coefficient path has a significant effect, except for the indirect effect between service quality and patient loyalty through value. Hospital management practitioners should focus on developing service quality improvement strategies that are able to create value for patients so as to increase satisfaction and ultimately encourage and maintain patient loyalty.Hospitals can take advantage of this research model as a self-evaluation instrument to achieve patient loyalty so as to increase hospital revenue and reputation.